(untitled) - Baker, Keith; 1953- (San Diego, 2004)
Mr. and Mrs. Green, two alligators, spend time together fishing, painting, and going to the park.
"Book two."
Keywords: Fiction; Alligators; Fiction; Parks; Fiction; Jellybeans; Fiction; Fiction; Fishing; Painting